Functional Abnormalities of the Liver in Diabetic Patients with and without Hepatitis C - Idkhuu, Altantuya; Sevjid, Badamjav; Sonomtseren, Sainbileg; Dungubat, Erdenetsogt; Duger, Davaadorj; Namdag, Bira; Radnaa, Otgonbayar (Central Asian Journal of Medical Sciences, 2019)
Objective: We aimed to compare liver function of diabetes mellitus patients with and without viral hepatitis C using the non-alcoholic fatty liver disease fibrosis score, aspartate transaminase to platelet ratio index, Fibrosis-4 Index, Mac-2-binding protein biomarker and ultrasonic liver stiffness measurements. Methods: The study was conducted based on convenience sampling of 123 patients. Slightly more than half of the study participants were male (53%, n=64). Thirty-three of the diabetics with hepatitis (mean age 52.31±9.8 years) and 90 diabetics without hepatitis (mean age 53.26±8.58) agreed to participate. Anthropometric measurements, non-alcoholic fatty liver disease fibrosis score, aspartate transaminase to platelet ratio index, Fibrosis-4 Index, Mac-2-binding protein biomarker, and ultrasonic transient elastography measurements were compared using independent t-tests for continuous variables and Wilcoxon rank sum tests for ordinal variables. Results: The median values of the Fibrosis-4 Index for those with and without hepatitis C were 1.3 vs. 0.9 (p<.05), Mac-2-binding protein biomarker 2.0 vs. 1.3 (p<.0001), ultrasonic liver stiffness measurements 10.3 vs. 6.9 (p<.0001), aspartate transaminase to platelet ratio 0.6 vs. 0.3 (p<.001), and Non-alcoholic fatty liver disease fibrosis scores were -0.2 vs. -0.9 ( p<.004), respectively Conclusions: Diabetic patients with hepatitis had statistically significantly higher Mac-2-binding protein biomarker, NAFLD Fibrosis Scores than patients without hepatitis. However, other fibrosis test results were similar in diabetic patients with hepatitis and without hepatitis C.